Interpersonal Function of Joe Biden’s Victory Speech (Systemic Functional Linguistics View) - Darong, Hieronimus Canggung (LPPM Undiksha, 2021)
Text analysis was mainly concerned with the ideational function and textual function. Besides, macro aspect has been regarded as the most text structure examined in previous studies. Regardless of those three aspects, this study focused on the interpersonal function analysis of political speech text, by taking an example of Joe Biden’s victory speech. The purposed theory namely Systemic Functional Linguistics theory (SFL) was then applied to analyze the text. The analysis was conducted by modifying the speech text into clauses which were subsequently analyzed in accordance with the goal of the analysis. Data analysis revealed that the speech established an intimate relationship and a close distance with the audience. As such, the speaker enables to gain support and exchange information through the use of linguistics resources namely declarative clause in the mood structure, modality, and pronoun